Regional inequality in Europe: evidence, theory and policy implications. (27th April 2018) - Iammarino, Simona; Rodriguez-Pose, Andrés; Storper, Michael
Abstract: Regional economic divergence has become a threat to economic progress, social cohesion and political stability in Europe. Market processes and policies that are supposed to spread prosperity and opportunity are no longer sufficiently effective. The evidence points to the existence of several different modes of regional economic performance in Europe, responding to different development challenges and opportunities. Both mainstream and heterodox theories have gaps in their ability to explain the existence of these different regional trajectories and the weakness of the convergence processes among them. Therefore, a different approach is required, one that strengthens Europe's strongest regions but develops new approaches to promote opportunity in industrial declining and less-developed regions. There is ample new theory and evidence to support such an approach, which we have labelled 'place-sensitive distributed development policy'.